Multiple endocrine neoplasia type 1. - Pannett, A; Thakker, R (1999)
Combined clinical and laboratory investigations of multiple endocrine neoplasia type 1 (MEN1) have resulted in an increased understanding of this disorder which may be inherited as an autosomal dominant condition. Defining the features of each disease manifestation in MEN1 has improved patient management and treatment, and has also facilitated a screening protocol to be instituted. The application of the techniques of molecular biology has enabled the identification of the gene causing MEN1 and the detection of mutations in patients. The function of the protein encoded by the MEN1 gene has been shown to be in the regulation of JunD-mediated transcription but much still remains to be elucidated. However, these recent advances provide for the identification of mutant MEN1 gene carriers who are at a high risk of developing this disorder and thus require regular and biochemical screening to detect the development of endocrine tumours.